The Privatization of Education and its Implications for Latinos/as - Rosaura Sánchez; Beatrice Pita (Revue LISA)
The demographic growth of Latinos in the U.S. comes amidst a growing gap in access to education. Especially crucial to consider for this growing population is the neoliberal restructuring of kindergarten to university education that is leading to a growing emphasis on the privatization of higher education and the transformation of public education into a profit-driven domestic business opportunity. With rising tuition at universities and colleges and the increased technological and market aspects of schooling, only families residing in well-to-do communities will have access to what previously was deemed a civil right, the right to both a public and a first-class education.